2017
DOI: 10.1186/s13065-017-0339-4
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis, characterization and in vitro antimicrobial activity of novel fused pyrazolo[3,4-c]pyridazine, pyrazolo[3,4-d]pyrimidine, thieno[3,2-c]pyrazole and pyrazolo[3′,4′:4,5]thieno[2,3-d]pyrimidine derivatives

Abstract: BackgroundSome novel substituted pyrazolone, pyrazolo[3,4-c]pyridazine, pyrazolo[3,4-d]pyrimidine, pyrazolo[3,4-d]thiazolo[3,2-a]pyrimidinone, thieno[3,2-c]pyrazole and pyrazolo[3′,4′:4,5]thieno[2,3-d]pyrimidine derivatives have been reported to possess various pharmacological activities like antimicrobial, antitumor and anti-inflammatory.ResultsA novel series of azoles and azines were designed and prepared via reaction of 1,3-diphenyl-1H-pyrazol-5(4H)-one with some electrophilic and nucleophilic reagents. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Abdel Reheim et al 79 reported that the reaction of diphenylpyrazolone 149 with cyanoacetic hydrazide and elemental sulfur in DMF containing a catalytic amount of piperidine yielded 5-amino-1,3-diphenyl-1Hthieno[3,2-c]pyrazole-6-carbohydrazide (150) (Scheme 45).…”
Section: Scheme 44mentioning
confidence: 99%
“…Abdel Reheim et al 79 reported that the reaction of diphenylpyrazolone 149 with cyanoacetic hydrazide and elemental sulfur in DMF containing a catalytic amount of piperidine yielded 5-amino-1,3-diphenyl-1Hthieno[3,2-c]pyrazole-6-carbohydrazide (150) (Scheme 45).…”
Section: Scheme 44mentioning
confidence: 99%
“…After the publication of this work [ 1 ] it was noticed that on page 3 of the article beginning in the paragraph—‘Hydrazide 14 is used as a key producer…’ the compound—“Not ethyl- N ′-5-amino-1,3-diphenyl-1 H -thieno[3,2- c ]pyrazole-6-carbonylformohydrazonate” should be deleted. Also on page 10 of the PDF beginning in paragraph—‘Synthesis of 5-amino-…’ the compound—“Not ethyl- N ′-5-amino-1,3-diphenyl-1 H -thieno[3,2- c ]pyrazole-6-carbonylformohydrazonate” should be deleted.…”
Section: Correction To: Chemistry Central Journal (2017) 11:112 1011mentioning
confidence: 99%
“…Celecoxib and lonazolac are used as anti-inflammatory drugs, fipronil acts as an insecticide, dipyrone is a promising analgesic and antipyretic molecule [ 8 ], and sildenafil is used for erectile dysfunction treatment, all of these drugs are pyrazole based compounds [ 9 ]. Fused-pyrazoles have been found to exhibit several biological properties like anti-inflammatory [ 10 ], anti-viral [ 11 ], anti-tumor [ 12 ], anti-microbial [ 13 ], and antiprotozoal [ 14 ]. In addition, many fused-pyrazoles have shown significant anti-human immunodeficiency virus (HIV) properties [ 15 ].…”
Section: Introductionmentioning
confidence: 99%